HUBUNGAN ANTARA MOTIVASI KERJA DENGAN DISIPLIN KERJA PEGAWAI RSJ DAERAH ATMA HUSADA MAHAKAM SAMARINDA - Kirana, Delisa Athiah (MOTIVASI, 2013)
AbstractHigh work discipline on an employee comes down from a high motivation to work anyway. This is so that the performance of employees can be more productive.The study consisted of a single dependent variable, ie, work discipline and one independent variable, namely the motivation to work. The data was collected using a scale. The subjects in this study were employees RSJD Atma Husada Mahakam totaling 100 people. Data analysis techniques used were correlation. These results indicate there is a significant relationship between work motivation with employee discipline with correlation values: 0.827 and 0.684 R Square value indicates, that motivation affects up to 68.4% of labor discipline.